Modelling, analysis and containment of passive worms in P2P networks. (1st January 2014) - Yang, Wei; Gao, Yong-peng; Zhu, Zhi-liang; Chang, Gui-ran; Yao, Yu
Passive worms continue to pose major threats to the security of internet. In this paper, we tackle the issue by modelling and analysis passive worm propagation which is useful to understand how particular factors can affect their propagation and designing effective containment strategies within P2P networks to suppress worm propagation. In particular: 1) we propose two passive worm mathematic models: a static attack model and a dynamic attack model, and study the sensitivity of worm propagation with various parameters; 2) we conduct a detailed analysis to analyse the attack models and the basic reproduction number R 0 ; 3) finally, we design and evaluate containment strategies to combat passive worms. The simulation results verify the effectiveness of our model, the value of basic reproduction number have significant impacts on worm spread. We also find that our proposed containment strategies can effectively combat passive worms.